Guideline Improvement for Health Behavior Modification to Promote Self-Efficacy of Pre-Diabetic Patients at a Community in Kalasin Province - Thiputai, Phongsatorn; Limtragool, Petchsavai (Journal of Research in Nursing-Midwifery and Health Sciences, 2019)
This action research was conducted to study behaviors, self-efficacy and factors of health behavior of pre-diabetic patients and to guideline improvement for health behavior modification in the context. The target group consisted of 25 pre-diabetic patients, 7 family caregivers,10 public health volunteers, 3 community leaders and 1 health officer from Health Promoting Hospital. Qualitative data were analyzed using content analysis. Quantitative data were analyzed using frequency, percentage mean and standard deviation. The result showed that the overall health behavior of pre-diabetic patients were middle level (M =2.94) and the perception of self-efficacy was high level (M =3.25). There were 4 impact factors to health behavior consisted of : 1) Individual factors, 2) Environmental factors, 3) Family caregiver, and 4) Community participation factors. The guideline improvement as follow; 1) The activity to exchange the knowledge and plan to guideline improvement for health behavior modification., 2) The workshops to educate and promote skill., 3) The activity to exchange the knowledge with pre-diabetic patients model, 4) The activity to practice and develop skill to continue. The overall activities were supported from family caregiver who prepared menu of healthy food, activated and encouragement, 5) The home visit activity from health officer and public health volunteer., 6) The community leaders gave the knowledge and to assist equipment and place for exercise., and 7) The health officer had a guideline for health behavior modification.The evaluation revealed as the following; 1) Pre-diabetic patients had more the mean score in health behavior and perception of self-efficacy (M =3.38, 3.56). Thus, nurse should apply this guideline improvement in the closet context by family and community participation.